Short pulse radiation from an energy-chirped electron bunch in a soft X-RAY FEL - Martin, I; Bartolini, R (2010)
The production of short pulse radiation of 1fs or below would open up many new areas of research. Saldin et al recently proposed a scheme to generate such pulses, in which a laser pulse consisting of only a few optical cycles is used to give a short energy chirp to the electron bunch and uses a tapered undulator to compensate the chirped region. In this paper we study the application of this scheme to a soft x-ray free electron laser, including the results of full start to end simulations and an assessment of the sensitivity to jitter.